1999
DOI: 10.1159/000017375
|View full text |Cite
|
Sign up to set email alerts
|

Origin of Renewed Spinal Ganglia during Tail Regeneration in Urodeles

Abstract: The source of the cells which form the spinal ganglia within the regenerating urodele tail is not yet indisputably known. Classical and modern experimental approaches trace the spinal cord as the most probable source. The aim of the present study was to further investigate this item by conventional histology, counting of mitotic figures, and estimating the labeling index. The main results can be summarized as follows: (a) The regenerated part of the tail contained only two bilaterally asymmetrical pairs of gan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…2000). Following the first week of regeneration, ependymal cells differentiate into new CNS neurons and peripheral ganglia, reconnecting the spinal cord to the body periphery and recovering function (Koussoulakos et al. 1999).…”
Section: Resultsmentioning
confidence: 99%
“…2000). Following the first week of regeneration, ependymal cells differentiate into new CNS neurons and peripheral ganglia, reconnecting the spinal cord to the body periphery and recovering function (Koussoulakos et al. 1999).…”
Section: Resultsmentioning
confidence: 99%
“…It is critical to understand the cell source for the newly regenerated central and peripheral nervous system tissue. In 1988, Geraudi et al studied the formation and origin of spinal ganglia after regeneration in a newt ( Notophthalmus viridescens ) and concluded that no cells resembling neural crest cells contribute to the generation of the dorsal root ganglia (Geraudie et al , ), which was supported by histological analyses (Arsanto et al , ; Koussoulakos et al , ). Benraiss et al furthered the efforts in characterizing cells of the salamander ( Pleurodeles waltl ) CNS by establishing cell lines from primary spinal cord cell cultures and grafting labeled cultured cells back into regenerating tails.…”
Section: Ependymoglial Cell Regeneration and Neurogenesismentioning
confidence: 98%
“…When a lower motor neuron is destroyed, the classical notion states that the corresponding muscle fibers usually become permanently paralyzed. This might not be entirely true, since data are continuously accumulating that support possibilities for lower motor neuron restoration [26, 27]. However, when an upper motor neuron is destroyed, then the corresponding lower, intact motor neuron does not receive adequate messages, so that the corresponding muscle fibers do not receive the message of voluntary contraction and are regarded as paralyzed, which means that they cannot contract under voluntary control [28].…”
Section: The Revelation Of the Swan: Clinical Exploitation Of The Musmentioning
confidence: 99%